Foot strike pattern in sport shoes with different construction / Soňa Jandová...[et al.] - Jandová, Soňa (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Shoe type and their hardness play an important role in the characteristics of gait cycle. Runners usually use a conventional running shoes (CRS) and also in the last years' minimalist running shoes (MRS) with a thin, flexible outsole or they run barefoot. The type of shoes reportedly affects the magnitude of the vertical ground reaction forces when running The aim of this study was to analyse foot strike pattern according to plantar pressure distribution and dynamic characteristics of running gait in a group of recreational runners (8 men and 7 women; mean±SD; age = 34.6±6.2 years, body height = 1.81±0.08 m, body weight = 68.10±8.9 kg) when using minimalist and conventional running shoes. The Pedar system (Pedar-X®, Novel, Munich, Germany) with measuring insoles was used to record plantar pressure distribution and vertical ground reaction forces under the foot, heel, midfoot and forefoot. For the same type of foot-strike pattern, impact forces are higher for MRS than for CRS, which is why runners using MRS modify their foot-strike pattern with the aim of reducing these impact forces. The foot- strike pattern changed in 5 runners when using minimalist shoes. The foot strike pattern shifted from middle-foot strike to forefoot strike or from rear-foot strike to middle-foot strike when running in MRS. Plantar pressure distribution was different when running in MRS and in CRS. When running in MRS the Peak pressure values under the foot were significantly higher than values when using CRS. Peak pressure values and vertical ground reaction forces under the heel were in MRS higher only in a group of rear-foot strikers. The values of Peak pressure and vertical ground reaction forces related to CRS were in the area of the midfoot and forefoot higher, but the differences were not statistically significant (p > 0.05; n = 15).